Short term outcome of autologous whole blood injection in untreated tennis elbow - Dware, Prakash; Paudel, Mahendra; lama, Pemba; Chandra Amatya, Shiva; Bajracharya, Mangesh (Journal of Chitwan Medical College, 2024)
Background: Tennis elbow is a condition characterized by pain and tenderness around the lateral side of elbow joint. Autologous blood injection has been reported for the treatment as it contains various growth factors. The aim of the study is to evaluate the short-term outcome and effectiveness of autologous blood injection in untreated tennis elbow. Method: This prospective case study conducted from Mar 2022 to May 2023 after ethical clearance. Patient attending orthopedics outpatient department, People’s Dental College and Hospital with tennis elbow not treated previously and visual analogue scale pain score more than 40 were included by convenience sampling. The pain scores and Nirschl staging were calculated before autologous whole blood injection and subsequently at 2 weeks, 4 weeks and 3 months after injection. Data analysis was carried out using SPSS version 20. Pre- and post-injection pain score and Nirschl stages were compared. A p<0.001 was considered statistically significant. Result: In study of total of 28 patients, the median pain score before autologous blood injection and 3 months after injection was 80 (Q1-Q3, 70- 80) and 10 (Q1-Q3, 10-20) respectively with p<0.001. Similarly, the Nirschl stage before autologous blood injection and 3 months after injection was 6 (Q1-Q3, 5.3-6.8) and 2 (Q1-Q3, 1-3) respectively with p<0.001. Conclusion: The findings of the study shows that autologous whole blood injection significantly decreased the pain and can be considered an effective treatment option for untreated tennis elbow.